Misconception Of Junior High School Students On Two-Dimentional Figure Materials - Budiarto, Mega Teguh; Khabibah, Siti; Firdaus, Andi Mulawakkan (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2020)
This research is a qualitative descriptive study that aims to describe the misconceptions of junior high school students on the material of flat shapes especially geometry of rectangular flat shapes. The subjects of this study were three students who had the most misconceptions from all students in the class. Students' misconceptions in this study were analyzed using a written misconception test with the CRI (Certainty of Response Index) method and continued with interviews to find out the cause of the misconceptions that occurred. Based on the results of data analysis the three subjects showed almost the same misconception. The first misconception experienced by students on rectangular flat figure material lies in the definition of rectangular flat figure. Students' misconceptions in defining lie in a flat shape that has the same side of length, four corners, and two diagonals that form a right angle. This shows that students only choose rectangular regular shapes. In addition, students also experience misconceptions in distinguishing between sides and ribs. The second misconception, lies in the concept of the properties of a rectangular flat shape especially rectangular. Students assume that the rectangle always has an elongated shape without regard to its properties. Furthermore, there is a misconception when showing another wake. Students assume that the ladder is an oblique rectangle. In addition, if a rectangle has a different position or irregular shape then it is not called a rectangle. The cause of the misconception that occurs is the ability to understand the concepts and images given to the problem